Retrieval of Inferior Vena Cava Filters: Technical Considerations - Laws, James L. (Semin Intervent Radiol, 2016)
Placement of retrievable inferior vena cava filters has seen rapid growth since their introduction into clinical practice. When retrieved, these devices offer the notional benefit of temporary protection from pulmonary embolism related to lower extremity deep venous thrombosis, and mitigation of filter-related deep venous thrombosis. When promptly removed after the indication for mechanical prophylaxis is no longer present, standard endovascular retrieval techniques are frequently successful. However, the majority of these devices are left in place for extended periods of time, which has been associated with greater device-related complications when left in situ, and failure of standard techniques when retrieval is attempted. The development of advanced retrieval techniques has had a positive impact on retrieval of these embedded devices. In this article, technical considerations in the retrieval of such devices, with an emphasis on advanced techniques to facilitate retrieval of embedded devices, are discussed.